2014
DOI: 10.1021/jp503510x
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Micro/Nanocrystals with Tunable Exposed (0001) Facets for Enhanced Catalytic Activity on the Thermal Decomposition of Ammonium Perchlorate

Abstract: ZnO micro/nanocrystals with different percentages of the exposed (0001) facets were synthesized by a facile chemical bath deposition method. Various characterizations were carried out to understand the relationship between particle shape, exposed (0001) facets, and catalytic activity of ZnO nanocrystals for the thermal decomposition of ammonium perchlorate (AP). An enhancement in the catalytic activity was observed for the ZnO micro/nanocrystals with a higher percentage of the exposed (0001) facets, in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…Exept for the above mentioned energy related thermo-catalytic reactions, morphologycontrolled ZnO was also applied in environment pollutant removal processes. For example, Tang et al studied the effects of exposed (0001) facets over ZnO micro/nanocrystals on the catalytic performance of thermal decomposition of ammonium perchlorate (AP) [149]. It was found that a higher percentage of exposed (0001) facets leads to lower activation energy of AP decomposition.…”
Section: Other Thermo-catalytic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exept for the above mentioned energy related thermo-catalytic reactions, morphologycontrolled ZnO was also applied in environment pollutant removal processes. For example, Tang et al studied the effects of exposed (0001) facets over ZnO micro/nanocrystals on the catalytic performance of thermal decomposition of ammonium perchlorate (AP) [149]. It was found that a higher percentage of exposed (0001) facets leads to lower activation energy of AP decomposition.…”
Section: Other Thermo-catalytic Reactionsmentioning
confidence: 99%
“…Highly exposed (0001) facets will promote perchloric acid adsorption and diffusion and facilitate the formation of active oxygen species, leading to the more complete oxidation reaction of ammonia in the catalytic decomposition of AP [149] Catalysts 2016, 6, 188…”
Section: Co Oxidationmentioning
confidence: 99%
“…[154] The high reactivity of the polar (0001) facets has also been identified in the decompositionofperchloric acid; the activity linearly increases as the fraction of exposed (0001)f acets increases (Figure 9a-d). [155] Theoretical calculations evidence that this polar facet not only accelerates the adsorption and diffusiono ft he reactant but also facilitates the generation of active oxygen species.…”
Section: Zno Nanoparticlesmentioning
confidence: 99%
“…Reprinted with permission from Refs. [155,156].Copyright 2014 and 2013,American Chemical Society. ure 10 a, b).…”
Section: Zno-supported Metal Catalystsmentioning
confidence: 99%
“…Materials qualified as burn rate modifiers for ammonium perchlorate (AP) based propellants are mainly transition metal oxides like, iron (III) oxide, cobalt (III) oxide, manganese (IV) oxide and copper (II) oxide, and mixed metal oxides like copper chromite etc. [3][4][5][6][7][8][9][10][11]. The physical characteristics of the metal oxides such as, particle size, surface area and defects in the crystalline structure and chemical characteristics such as oxidation state and chemical composition affect its catalytic activity for the thermal decomposition of ammonium perchlorate which in turn affects the burn rate of AP based propellants.…”
Section: Introductionmentioning
confidence: 99%